Urban and Groundwater Microplastic Contamination: Sources, Distribution, Impacts, and Remediation Technologies - Hussain, Noor Nafsiah Mohamad; Lopez-Martinez, Flavio (Civil and Sustainable Urban Engineering, 2024)
The presence of microplastics (MPs) in urban environments and groundwater systems has garnered significant global attention due to the critical role groundwater plays as a primary freshwater source. This review paper aims to comprehensively examine the sources, distribution, movement, and environmental impact of MPs, particularly focusing on urban areas and groundwater contamination. Special emphasis is placed on MPs originating from landfill leachate and their distribution along Malaysia's beaches. The paper also discusses the movement patterns of MPs, providing mathematical models for their migration. The environmental and health impacts of MPs, including soil degradation, toxicity in agricultural crops, and heavy metal adsorption, are analyzed. Additionally, current remediation technologies such as reverse osmosis, microbial exploitation, and ozonation are evaluated, with recommendations for combining different methods to enhance MP removal effectiveness. The involvement of the general public, socio-economic sectors, tourism, and waste management companies is highlighted as crucial for addressing this pervasive issue.